The Relationship between Knowledge Levels, Physical Activity Levels, and the Incidence of Type 2 Diabetes Mellitus in Individuals Aged ≥40 Years within the Anak Tuha Public Health Center Service Area in 2024 - Arni Despa P; Alifiyanti Muharramah; Dera Elva Junita; Desti Ambar Wati (Jurnal EduHealth, 2026)
Type 2 diabetes mellitus is a chronic condition in which the body cannot use insulin effectively. Risk factors for type 2 diabetes mellitus include factors that can be changed (knowledge, nutritional intake, physical activity and stress levels) and cannot be changed (age, gender, and genes). The purpose of the study was to determine the relationship between the level of knowledge, the level of carbohydrate and fat adequacy, the level of physical activity and the level of stress with the incidence of type 2 diabetes mellitus at the age of ≥40 years in the working are of Anak Tuha Public Health in 2024. The quantitative research method used a case-control design with a population of 343 patients, while the sample consisted of 72 people, 36 cases and 36 control groups. The study was conducted on July 17 - August 17, 2024, using a purposive sampling technique. Instruments used were questionnaires, 24-hour Recall Forms, and easy-touch glucometer devices. The bivariate tests used were the chi-square test and the Mann-Whitney test. The results showed that there was a significant relationship between the level of knowledge (p-value=0.000), the level of physical activity (p-value=0.00) and the incidence of type 2 diabetes mellitus.